2020
DOI: 10.1515/corrrev-2019-0111
|View full text |Cite
|
Sign up to set email alerts
|

The roles of biomolecules in corrosion induction and inhibition of corrosion: a possible insight

Abstract: Biofilms cause huge economic loss to the industry through corrosion. A deeper understanding of how biofilms form, develop and interact will help to decipher their roles in promoting and inhibiting corrosion, thus in controlling it. The present review explores most mechanisms of biofilm development and maintenance with particular emphasis on the roles of the biomolecules characteristic of biofilms, including exopolysaccharides (EPSs), proteins/enzymes, lipids, DNA and other metabolites in the corrosion process.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 123 publications
0
7
0
Order By: Relevance
“…Cluster 1 (red) comprised 21 genes, primarily participating in metal ion binding. Karn et al, 2020, reported that the binding of the metal ions with the biofilm matrix of the bacteria led to the formation of complexes that participated in the process of electron transfer, influencing the corrosion reactions [ 22 ]. Cluster 2 (green) consists of 16 genes associated with it, mainly involved in electron transfer and cellular respiration activities.…”
Section: Resultsmentioning
confidence: 99%
“…Cluster 1 (red) comprised 21 genes, primarily participating in metal ion binding. Karn et al, 2020, reported that the binding of the metal ions with the biofilm matrix of the bacteria led to the formation of complexes that participated in the process of electron transfer, influencing the corrosion reactions [ 22 ]. Cluster 2 (green) consists of 16 genes associated with it, mainly involved in electron transfer and cellular respiration activities.…”
Section: Resultsmentioning
confidence: 99%
“…In bacterially-dominated biofilms, reviewed by Karn et al (52) (2020) for their role in promotion or inhibition of corrosion, carbohydrates are generally the most abundant constituents, accounting for 40-95% by mass, while proteins typically contribute 1-60%, lipids 1-40%and nucleic acids 1-10%. The biofilm matrix acts as a recycling centre, by preventing the molecular products of live cells from dispersing and becoming lost to the consortium (135) (122) (Flemming and Wingender, 2010).…”
Section: Quorum Sensingmentioning
confidence: 99%
“…Like marine organic aggregates (MOAs), sewage sludge organic aggregates (SOAs) consist mainly of bacteria and diverse debris held together with loosely-bound EPS, in a slimy matrix of closely-bound or unbound EPS. The more concentrated nature of SOAs sewage sludge compared with the ocean, together the need to dewater it for economical transport and disposal, drives lively research activity on the rheology and surface science of SOAs (138) (Zhang et al, 2018), as well as on ecological chemistry of SOAs and biofilms (139) (52) (Lear, 2016;Karn et al, 2020). This activity provides results and expertise with a strong potential to inspire and guide research on MOAs.…”
Section: Quorum Sensingmentioning
confidence: 99%
“…In many other consortia, such as biofilms [50][51][52], lake and marine organic aggregates [53,54], however, cohesion is achieved by physical processes such as stickiness [55], gelling [56] or increased viscosity [57], mediated by exopolymeric substances (EPS). Schwartz et al [33] suggested that consortia with more elements than 3 are likely to exist, but that the number of degrees of freedom would make their existence difficult to prove.…”
Section: Consortia Structured By Rheological Properties Including Sti...mentioning
confidence: 99%
“…In bacterially dominated biofilms, reviewed by Karn et al [52] for their role in promotion or inhibition of corrosion, carbohydrates are generally the most abundant constituents, accounting for 40-95% by mass, while proteins typically contribute 1-60%, lipids 1-40% and nucleic acids 1-10%. The biofilm matrix acts as a recycling center, by preventing the molecular products of live cells from dispersing and becoming lost to the consortium [134].…”
Section: Quorum Sensingmentioning
confidence: 99%